2020
DOI: 10.3390/v12050543
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNAs in Host Defense against Infectious Bursal Disease Virus (IBDV) Infection: A Hidden Front Line

Abstract: Infectious bursal disease (IBD) is an acute, highly contagious and immunosuppressive avian disease caused by infectious bursal disease virus (IBDV). In recent years, remarkable progress has been made in the understanding of the pathogenesis of IBDV infection and the host response, including apoptosis, autophagy and the inhibition of innate immunity. Not only a number of host proteins interacting with or targeted by viral proteins participate in these processes, but microRNAs (miRNAs) are also involved in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 127 publications
(160 reference statements)
0
16
0
Order By: Relevance
“…For instance, gga-miR-1723, gga-miR-222b-3p, gga-miR-1782, gga-miR-449a, and gga-miR-1563 exhibited significantly varied expression levels following IBV infection in chicken kidneys [45]. Interestingly, we also found that gga-miR-130b-3p, gga-miR-142-5p, gga-miR-454-3p, gga-miR-27b-3p, gga-miR-1635, and gga-miR-155 were DE in vvIBDV-infected cells [21,29]. However, previously reported highly expressed miRNAs were not significantly DE in vvIBDV-infected BF.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For instance, gga-miR-1723, gga-miR-222b-3p, gga-miR-1782, gga-miR-449a, and gga-miR-1563 exhibited significantly varied expression levels following IBV infection in chicken kidneys [45]. Interestingly, we also found that gga-miR-130b-3p, gga-miR-142-5p, gga-miR-454-3p, gga-miR-27b-3p, gga-miR-1635, and gga-miR-155 were DE in vvIBDV-infected cells [21,29]. However, previously reported highly expressed miRNAs were not significantly DE in vvIBDV-infected BF.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, aberrantly expressed miRNAs in cells or tissues play a crucial role in virus-host interactions [20]. It has been reported that classical IBDV infection affects miRNA expression in DF-1 cells [21]. The discovery of miRNAs provides new insights into the mechanisms of gene regulation [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Some miRNAs could target viral genomes and proteins to suppress virus replication ( Wen et al, 2013 ). While, other miRNAs, like gga-miR-142-5p ( Ouyang et al, 2018 ), miRNA-16-5p ( Duan et al, 2020 ), may inhibit host defense and enhance virus replication and infection ( Li and Zheng, 2020 ). There is evidence that miRNAs exert antiviral effects on virus infection by modulation of certain immune and antiviral pathways, such as the janus kinase-signal transducer and activator of transcription (JAK-STAT), toll-like receptor, and mitogen-activated protein kinase signaling pathways ( Lin et al, 2016 ; Fu et al, 2018 ).…”
Section: Anti-virusmentioning
confidence: 99%
“…JARQ 56 (1) 2022 N. Tanimura on various aspects of IBD, including the acute form of IBD caused by very virulent IBDV (vvIBDV) (van den Berg 2000), host-pathogen interactions (Ingrao et al 2013, Li & Zheng 2020, Qin & Zheng 2017, pathogenesis and immunosuppression (Sharma et al 2000), the current status of vaccines against IBD (Müller et al 2012), and management strategies (Dey et al 2019). However, the molecular basis for the pathogenicity of the virus has not been fully determined (Qi et al 2013, Eterradossi & Saif 2020, and the pathogenesis of IBD remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%